1987
DOI: 10.1007/bf00016438
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the Agrobacterium tumefaciens octopine Ti-plasmid left and right T-region border fragments

Abstract: SummaryBorder fragments of the octopine Ti-plasmid were tested for their ability to restore tumorigenicity of an avirulent mutant carrying a deleted right border. It was found that neither introduction of left border fragments nor that of small right border fragments at the position of the deletion resulted in a complete restoration of oncogenicity. However, insertion of a larger right border fragment in the deletion mutant gave fully oncogenic strains. In the latter case sequences to the right side of the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
1
32
1
Order By: Relevance
“…Wild-type levels of tumorigenesis require the right border repeat and a flanking sequence called overdrive (28,42). Although it plays a nonessential role, the overdrive sequence enhanced T-DNA transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type levels of tumorigenesis require the right border repeat and a flanking sequence called overdrive (28,42). Although it plays a nonessential role, the overdrive sequence enhanced T-DNA transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The T-DNA borders are cis-acting components that functionally define the T-DNA region. The rightward border repeat is required in its native orientation together with its flanking sequences (overdrive) for efficient transformation of plant cells (14,15,28,29,42,44).…”
mentioning
confidence: 99%
“…This enhancer has been found to be specifically recognized by VirC1 protein (Toro et al, 1989). Deletion of virC operon is followed by attenuation of virulence of the Agrobacterium strains (van Haaren at al., 1987;Rogowsky et al, 1990). …”
Section: Generation Of T-dna Transfer Complexmentioning
confidence: 99%
“…This is not the only reason for the difference in activity though. For the octopine Ti plasmid it has been shown that an extra sequence is present next to the right border repeats (but not near left border repeats) which stimulates the transfer process [19,23]. This T region transfer enhancer has been called overdrive [19].…”
Section: Successful Transformation Of Plant Cells Bymentioning
confidence: 99%
“…For cloning purposes the vectors plC19R and plC20R and the shuttle vector pRAL5200 were used [13,23]. A synthetic right border fragment (SRB) of the octopine pTi15955 TL region and the synthetic right border of the nopaline pTiT37 plasmid T region were inserted in plC19R as Sal 1-Hind III fragments.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%